Catalytic activation of a single C–F bond in trifluoromethyl arenes. Issue 1 (23rd October 2015) - Dang, Hester; Whittaker, Aaron M.; Lalic, Gojko
Abstract : Catalytic activation of a single C–F bond in a trifluoromethyl group was used to accomplish highly selective monodefluorination of trifluoromethyl arenes. An investigation of the reaction mechanism suggests the formation of an unexpected intermediate and provides evidence for an unusual reaction pathway responsible for the observed selectivity. Abstract : Synthetic methods for the direct transformation of ArCF3 to ArCF2 R would enable efficient diversification of trifluoromethyl arenes and would be of great utility in medicinal chemistry. Unfortunately, the development of such methods has been hampered by the fundamental properties of C–F bonds, which are exceptionally strong and become stronger with increased fluorination of the carbon atom. Here, we describe a method for the catalytic reduction of ArCF3 to ArCF2 H through a highly selective activation of a single C–F bond. Mechanistic studies reveal separate reaction pathways for the formation of ArCF2 H and ArCH3 products and point to the formation of an unexpected intermediate as the source of the unusual selectivity for the mono-reduction.